Pengaruh variasi penambahan serbuk grafit dalam pasir terhadap konduktivitas listrik beton K-350 (Effect of variations in the addition of graphite powder in sand to the electrical conductivity of K-350 concrete) - Fitri Anika; Djusmaini Djamas; - Ramli (PILLAR OF PHYSICS, 2015)
Concrete conductive using graphite powder as a conductive material has not been optimized in their use of construction materials. Therefore, be used graphite powder as an ingredient added in the sand for the manufacture of concrete that is conductive. So with the addition of graphite powder in the sand is expected to produce electrical conductivity in the concrete. This is caused by the addition of carbon (C) contained in graphite powder is able to conduct electricity through the cement paste and aggregate, thus increasing the electrical conductivity of concrete. Has been testing an electric conductivity in volume of concrete K-350 with the addition of graphite powder variation of 0%, 5%, 10%, 15% and 20% using the test method Four-Point Probe. Results of testing the value of the electrical conductivity in the volume of concrete for each successive age the age of 7 days is 0.0229 (Ω.m)-1, 0.0286 (Ω.m)-1, 0.0306 (Ω.m)-1, 0.0358 (Ω.m)-1, 0.0374 (Ω.m)-1. At the age of 14 days in a row is 0.0132 (Ω.m)-1, 0.0177 (Ω.m)-1, 0.0207 (Ω.m)-1, 0.0250 (Ω.m)-1, 0.0291 (Ω.m)-1. At the age of 21 days in a row is 0.0099 (Ω.m)-1, 0.0135 (Ω.m)-1, 0.0155 (Ω.m)-1, 0.0164 (Ω.m)-1, 0.0204 (Ω.m)-1. At the age of 28 days in a row is 0.0074 (Ω.m)-1, 0.0101 (Ω.m)-1, 0.0111 (Ω.m)-1, 0.0121 (Ω.m)-1, 0.0152 (Ω.m)-1. From this study it can be concluded that the addition of graphite powder variations can increase the value of the electrical conductivity in the volume of concrete K-350, but declined against the concrete. This is caused by the influence of water content owned concrete